Use of Pyrimisulfan and Penoxsulam in Turfgrass Systems - J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2017)
Pyrimisulfan + penoxsulam applications in ‘Meyer’ zoysiagrass and buffalograss resulted in excellent large crabgrass control and no turfgrass injury. Applications also do not have any negative influence on tested ornamental species.
Keywords: Pyrimisulfan; penoxsulam